Traditions apocryphes dans la Théosophie de Tübingen - Beatrice, Pier Franco (Apocrypha, 1996)
In this paper two passages of the so-called Tübingen Theosophy are taken into consideration. This work was written at the beginning of the sixth century by an, anonymous theologian well informed on Greek religious and philosophical traditions. The Byzantine compiler of the eighth century tells us that the author of the Theosophy had also used some apocryphal works : an attempt is made here to identify them. In the second passage, preserved in an original fragment, the author speaks about the provisional immortality of Elijah and Enoch. The analysis of these texts provides good arguments in favour of the monophysite origin of the Theosophy and confirms its attribution to Severus of Antioch.